Fundamental Characteristics of Bat Interferon Systems - Clayton, Emily; Munir, Muhammad (Frontiers in Cellular and Infection Microbiology, 2020)
Interferons are an essential component of the innate arm of the immune system and are arguably one of the most important lines of defence against viruses. The human IFN system and its functionality has already been largely characterised and studied in detail. However, the IFN systems of bats have only been marginally examined to date up until the recent developments of the Bat1k project which have now opened new opportunities in research by identifying six new bat genomes to possess novel genes that are likely associated with viral tolerance exhibited in bats. Interestingly, bats have been identified to possess the unique ability to establish a host-virus relationship where despite being infected, they exhibit limited signs of disease and still retain the ability to transmit the disease into other susceptible hosts. Bats are one of the most abundant and widespread vertebrates on the planet and host many zoonotic viruses that are highly pathogenic to humans. However, despite these factors, they remain one of the least extensively studied mammals in the laboratory and in literature. Several unique genomics, immunological and biological features are thought to underlie novel antiviral mechanisms of bats. This review aims to explore the bat IFN system and developments in its diverse IFN features, focusing mainly on the model species, the Australian black flying fox (Pteropus alecto), whilst also highlighting bat innate immunity as an exciting and fruitful area of research to understand their unique ability to control viral-mediated pathogenesis.